Temporal trends and predictors of time to coronary angiography following non-ST-elevation acute coronary syndrome in the USA. Issue 3 (May 2019) - Rashid, Muhammad; Fischman, David L.; Martinez, Sara C.; Capers, Quinn; Savage, Michael; Zaman, Azfar; Curzen, Nick; Ensor, Joie; Potts, Jessica; Mohamed, Mohamed O.; Kwok, Chun Shing; Kinnaird, Tim; et al.
Abstract : Objective: This study aims to investigate the temporal trends in utilization of invasive coronary angiography (CA) at different time points and changing profiles of patients undergoing CA following non-ST-elevation acute coronary syndrome (NSTEACS). We also describe the association between time to CA and in-hospital clinical outcomes. Patients and methods: We queried the National Inpatient Sample to identify all admissions with a primary diagnosis of NSTEACS from 2004 to 2014. Patients were stratified into early (day 0, 1), intermediate (day 2) and late strategy (day≥3) according to time to CA. Multivariable logistic regression was used to investigate the association between time to CA and in-hospital mortality, major bleeding, stroke and Major Adverse Cardiac and Cerebrovascular Events. Results: A total of 4 380 827 records were identified with a diagnosis of NSTEACS, out of which 57.5% received CA. The proportion of patients undergoing early CA increased from 65.6 to 72.6%, whereas late CA commensurately declined from 19.6 to 13.5%. Patients receiving early CA were younger (age: 64 vs. 70 years), more likely to be male (63.7 vs. 55.3%) and of Caucasian ethnic background (68.7 vs. 64.7%) compared with late CA group. Similarly, Women, weekend admissions and African Americans remain less likely to receive early CA. In-hospital mortality was lowest in the intermediate group (odds ratio=0.30, 95% confidence interval: 0.28–0.33). Conclusion: Use of early CA has increased in the management of NSTEACS; however, there remain significant disparities in utilization of an early invasive approach in women, African Americans, admission day and older patients in the USA. Abstract : Supplemental Digital Content is available in the text.